V-Y flap of advancement after the recurrence of perineal cancer: case report and literature review - Glayse June Sasaki Acacio Favarin; Eduardo Favarin; Luan Pedro Santos Rocha; Ives Alexandre Yutani Koseki; Fábio Yutani Koseki; Edson Rodrigues Garcia Filho (Revista Brasileira de Cirurgia Plástica)
INTRODUCTION: Anal cancer is a rare disease, with an increasing incidence. Flaps are complex options for closing large areas. The perineal region may be affected by extensive lesions that require the use of flaps for repair. CASE REPORT: A 56-year-old female patient with anal adenocarcinoma underwent abdominoperineal amputation surgery of the rectum with postoperative radiotherapy for 2 years. She had cutaneous recurrence of the neoplastic lesion with indication of surgical margin expansion to control the local recurrence. After extensive resection with safety margins of the skin defect, we selected double V-Y flap of length 15 cm each and a total thickness of the gluteal subcutaneous tissue (ST) to fill up the dead space caused by resection and advancement of the defect. Intravenous antibiotic prophylaxis and deep venous thrombosis prophylaxis were administered. The patient progressed well from the procedure, with no problems. DISCUSSION: A flap is a tissue that is mobilized based on vascular anatomy. Flaps based on the subdermal plexus include bipedicle, advancement (V-Y), rotation, and transposition flaps. Perineum reconstructions are often indicated for tumors, trauma, infections, burns, or pressure sores. The anal region is divided into the anal canal and the anal margin. Among the histological types of anal cancer, the most prevalent are squamous cell carcinoma (most common histology), adenocarcinoma, melanoma, small cell carcinoma, and sarcomas. The risk of regional recurrence after treatment can reach approximately 30% of cases and is the most frequent recurrence pattern.